2016
DOI: 10.1016/j.asr.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

The grand aurorae borealis seen in Colombia in 1859

Abstract: On Thursday, September 1, 1859, the British astronomer Richard Carrington, for the first time ever, observes a spectacular gleam of visible light on the surface of the solar disk, the photosphere. The Carrington Event, as it is nowadays known by scientists, occurred because of the high solar activity that had visible consequences on Earth, in particular reports of outstanding aurorae activity that amazed thousands of people in the western hemisphere during the dawn of September 2. The geomagnetic storm, genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
(51 reference statements)
1
13
0
1
Order By: Relevance
“…The figure indicates the eyewitnesses auroral (orange dots) and magnetic (blue dots) observations on 2 September 1859. These Mexican observations of the effects of the Carrington Event complement the records in other countries (Green et al, ), such as Guatemala (Ribeiro et al, ), Colombia (Moreno Cárdenas et al, ), Spain (Farrona et al, ), Australia (Humble, ), and East Asia (Hayakawa et al, ) among others, confirming that this was a global event with planetary repercussions.…”
Section: Observations Of the 1859 Aurora In Mexicosupporting
confidence: 74%
See 2 more Smart Citations
“…The figure indicates the eyewitnesses auroral (orange dots) and magnetic (blue dots) observations on 2 September 1859. These Mexican observations of the effects of the Carrington Event complement the records in other countries (Green et al, ), such as Guatemala (Ribeiro et al, ), Colombia (Moreno Cárdenas et al, ), Spain (Farrona et al, ), Australia (Humble, ), and East Asia (Hayakawa et al, ) among others, confirming that this was a global event with planetary repercussions.…”
Section: Observations Of the 1859 Aurora In Mexicosupporting
confidence: 74%
“…Green and Boardsen () plotted the auroral observations, finding the equatorward boundary as ∼18° in magnetic latitude (MLAT) on 2/3 September 1859. Hayakawa et al () and Moreno Cárdenas et al () surveyed historical reports from low‐magnetic latitude and confirmed the auroral visibility down to 19.9° in MLAT and 23.1° in MLAT, respectively.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Note that throughout this report, we use the terms "sunspot group" and "active region" as synonyms. We also recover and examine the contemporary auroral reports in the Russian and Japanese archival material, revise the temporal and spatial evolutions of the auroral visibility using known auroral reports (Farrona et al, 2011;González-Esparza & Cuevas-Cardona, 2018;Hayakawa et al, 2016, Hayakawa, Ebihara, Hand, et al, 2018Humble, 2006;Kimball, 1960;Moreno Cárdenas et al, 2016), and compare them with available magnetograms (Kumar et al, 2016;Nevanlinna, 2006Nevanlinna, , 2008. With this 10.1029/2019SW002269 Space Weather combined information, we contextualize the results in conjunction with those of the other extreme magnetic storms in observational history (see Chapman, 1957a).…”
Section: Introductionmentioning
confidence: 99%
“…Os efeitos dessa perturbação no campo magnético terrestre, ou tempestade magnética, foram rapidamente notados em escalas globais. Auroras boreais e austrais foram vistas em diversas regiões de baixas latitudes (menores que 60 • ), incluindo Havaí, Flórida, e Washington, D.C. nos Estados Unidos [23][24][25], México [26], Colômbia [27], Espanha [28], Austrália [29],Ásia Oriental [30] e Chile, Portugal, leste da Rússia, Austrália e Nova Zelândia [31]. A Fig.…”
Section: A Andorinha Solitária Do Verão De 1859unclassified